Structural and functional study of MACPF/CDC superfamily proteins - Ni, T (2016)
The thesis mainly focuses on structural study of proteins in membrane attack complex- perforin/cholesterol-dependent cytolysins (MACPF/CDC) superfamily, in particular, Astrotactins from human and perforin-like proteins (PLPs) from Toxoplasma and Plasmodium. Both of these subfamily proteins are implicated in human diseases and structurally uncharacterised before. Astrotactins (ASTNs) have been shown to play a crucial role in enabling neural migration along glial fibres. While ASTN1 directly forms contacts between the neuron and the fibre, ASTN2 is responsible for extracting ASTN1 from contacts at the lagging edge of the cell and recycling them to the leading edge. ASTN2 is associated with endosomes, with the majority of its structure (at the C-terminus) projecting into their lumen, anchored by a pair of transmembrane –-helices. Here we present the structure of this "endodomain" region of ASTN2, and find it to consist of a unique combination of polypeptide folds comprising a membrane attack com- plex/perforin (MACPF) domain, an EGF-like domain, a previously-unobserved form of fibronectin type III (Fn(III)) domain and an annexin-like domain. Taken together, the structural characterisation provides a framework for better understanding the mechanism of the ASTNs and related proteins in neural and other forms of vertebrate development. Perforin-like proteins from Toxoplasma and Plasmodium (TgPLP1 and PPLPs) are critical for normal life cycle progression of these parasites, and knockout out of any of them results in significant defects in their life cycle, entrapping the parasites within the host cells and thus limiting their ability to egress. Here we present the crystal structures of TgPLP1 MACPF domain and C-terminal domain at 2.0 Å and 1.1 Å, respectively. We also presents the MACPF domain assembled in helical and hexameric ring form, which indicates the possibility of pore-formation by 6 subunits. This is the first structure of perforin-like protein from Apicomplexan parasites and provides a structural basis to elucidate the function of PLPs in toxoplasmosis and malaria pathogenesis. The final section is a continuation of a previous study in our lab on pleckstrin homology (PH) domain of kindlins. We determined the crystal structure of kindlin-3 PH domain and characterised its lipid and membrane binding properties. Using nanodiscs incorporated with different lipids as model membrane system to study the interaction between inositol phosphate lipids and kindlin-3 PH domain, together ￼with molecular dynamic simulation studies (in collaboration with Mark Sansom’s group, University of Oxford), we propose that a subset of PH domains is able to bind to multiple inositol phosphates simultaneously and so via an avidity effect have its interaction with target membranes strengthened.